Keeping faith. Series 3 [videorecording (DVD)]. - Myles, Eve, 1978-; Jones, Mark Lewis; Daniel, Hannah, 1986-; Gravelle, Matthew (Acorn Media, 2021)
Faith attempts to navigate the disillusion of her marriage, while taking on an emotionally wrenching legal medical case involving a gravely ill young boy. Into this mix, Faith is confronted by a terrible and long buried figure from her past: her mother.